Multi-wavelength Erbium-doped fiber laser based on four-wave-mixing effect in single mode fiber and high nonlinear fiber - Wang, Pinghe; Weng, Danmei; Li, Kun; Liu, Yong; Yu, Xuecai; Zhou, Xiaojun (Optics express, 2013)
A multi-wavelength Erbium-doped fiber (EDF) laser based on four-wave-mixing is proposed and experimentally demonstrated. The 5 km single mode fiber in the cavity enhances the four-wave-mixing to suppress the homogenous broadening of the erbium-doped fiber and get the stable multi-wavelength comb. The lasing stability is investigated. When the pump power is 300 mW, the fiber laser has 5-lasing lines and the maximum fluctuation of the output power is about 3.18 dB. At the same time, a laser with 110 m high nonlinear fiber (HNFL) is demonstrated. When the pump power is 300 mW, it has 7-lasing lines (above -30 dBm) and the maximum fluctuation is 0.18dB.